Effect of Feeding Straw Based Complete Diet Supplemented with Thermotolerant Probiotic Yeast on Rumen Fermentation Pattern in Nellore Rams - Harikrishna, Ch.; Mahender , M. (International Journal of Livestock Research, 2021)
An experiment was conducted in a 4 x 4 LSD trial to find out the effect of thermotolerant probiotic yeast (Saccharomyces cerevisiae, OBV-9) on rumen fermentation pattern in Nellore rams (live weight 39.750.24 kg, 360.02 months age) fed with straw based complete diet. Probiotic yeast was supplemented at 0 (D1), 0.1 (D2), 0.2 (D3) and 0.3% (D4) level in the complete diet. Rumen liquor analysis revealed that, all the nitrogen fractions of rumen fluid (except food and protozoal nitrogen), pH and TVFA were significantly (P<0.01) higher on rations D2, D3 and D4 compared to D1. Time of sampling also had significant (P<0.01) effect on concentration of all rumen nitrogen fractions and TVFA, which peaked at 4 h post feeding, while ammonia nitrogen and pH were peaked at 2 h post feeding irrespective of rations. The study indicated that supplementation of thermotolerant yeast had favorable effect on pattern of nitrogen fractionalization, its absorption and utilization from the rumen in Nellore rams.